IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN SISWA DI SEKOLAH DASAR KOTA BAUBAU - Irsan Irsan; Syamsu Rijal (JKPD (Jurnal Kajian Pendidikan Dasar), 2020)
Serious problems in terms of discipline character education indicate the occurrence of undisciplined behavior in schools. Character education is happening again in the process of character formation. It could be that character education carried out so far is only at the knowledge stage, not yet reaching feelings and behaviors that have character. From a number of character values that need to be instilled, self-discipline is one of the important character values developed. Education in elementary schools is the first formal level of education that will determine the direction of potential development of students. Therefore, in elementary schools it is necessary to develop the character of student discipline optimally so that expectations at the next level of students already have a strong provision of disciplinary behavior. Given the importance of character education in the discipline of students in primary schools, various policies need to be carried out. This study uses a qualitative-descriptive analysis research method with induction logic. This study aims to describe a situation, describe and illustrate the implementation of character discipline education for students in Katobengke 1 Primary School, Buabau City. As for several policies that can be applied in schools, among others, planters and understanding of disciplined character education, establishing student discipline rules, teacher control in monitoring student disciplinary behavior at home, sharing school wall disciplinary messages, sharing school wall discipline messages, parents as supporters of their implementation disciplined character education in schools. Permasalahan serius dalam hal pendidikan karakter disiplin menunjukkan terjadinya perilaku tidak disiplin di sekolah. Pendidikan karakter yang terjadi merupakan again dalam proses pembentukan karakter. Bisa jadi pendidikan karakter yang dilakukan selama ini baru pada tahap pengetahuan saja, belum sampai pada perasaan dan perilaku yang berkarakter. Dari sejumlah nilai karakter yang perlu ditanamkan tersebut, disiplin diri merupakan salah satu nilai karakter yang penting dikembangkan. Pendidikan di sekolah dasar merupakan jenjang pendidikan formal pertama yang akan menentukan arah pengembangan potensi peserta didik. Oleh karena itu, di sekolah dasar perlu mengembangkan karakter disiplin siswa secara optimal sehingga harapannya di tingkat selanjutnya siswa sudah memiliki bekal perilaku disiplin yang kuat. Mengingat demikian pentingnya pendidikan karakter disiplin siswa di sekolah dasar, maka perlu dilakukan berbagai kebijakan. Penelitian ini menggunakan metode penelitian kualitatif-deskriptif analisis dengan logika induksi. Penelitian ini bertujuan untuk mendeskripsikan suatu keadaan, melukiskan dan menggambarkan implementasi pendidikan karakter disiplin siswa di Sekolah Dasar Negeri 1 Katobengke Kota Buabau. Adapun beberapa kebijakan yang bisa diterapkan di sekolah antara lain, penanam dan pemahaman pendidikan karakter disiplin, menetapkan aturan kedisiplinan siswa, kontrol guru dalam memantau perilaku kedisiplinan siswa di rumah, membagikan pesan kedisiplinan dinding sekolah, membagikan pesan kedisiplinan dinding sekolah, orang tua sebagai pendukung terlaksananya pendidikan karakter disiplin di sekolah.